Seed Recognition and Testing System with Android Application - Muhammad Fikri Mohamad Idris,; Chua King Lee, (Evolution in Electrical and Electronic Engineering, 2021)
The demand for image processing for seed testing in industrial agriculture has been increased over time. This project focuses on developing a system to identify the type of seed and detect disease of seed. The system utilized anomaly detection technique which is available in Android application to capture the image of an object and then compare with images that are being stored library to generate test result. The test result would indicate the type of seed being tested and define the health condition of the tested seed. The test measurement indicates that the system is able to recognize the seed in the image being captured, correctly the name of the seed under test and indicate the type of disease for the unhealthy seed.